Teachers content knowledge in generalizing mind maps of quadrilateral - Sahidin, L; Fuad, Y; Budiarto, M T (Journal of physics. Conference series, 2019)
This study aims to explain teacher content knowledge in generalizing mind maps of quadrilateral. This research use descriptive qualitative approach. The research subjects were 26 mathematics teachers (9 men and 17 women) who had taught at least 5 years and fulfilled the requirements for the teacher certification program. Knowledge of teacher content in generalizing quadrilateral concept maps was analyzed using De Villiers's framework on three types of definitions in geometry. The results showed that there were three types of knowledge of teacher content in defining rectangle, namely (1) fulfill the necessary requirements and sufficient conditions for minimal definition, (2) fulfill the necessary and sufficient condition but excessive requirements, and (3) not meet the necessary requirements and sufficient conditions. The mistakes shown by teachers are: incorrectly stating the nature or attributes; does not state sufficient conditions of definition; necessary conditions and sufficient conditions are excessive. The results show that there are two types of teachers content knowledge in generalizing hierarchically and partially mind maps.